Space, Time and Landscape. Representation of visual experiences and processes in analysis, design and planning of open spaces - Igualada, Javier Pérez; Vicente-Almazán, Gonzalo (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
The purpose of this paper is to examine the relationship between space, time and landscape from two different but complementary approaches: that of perception and that of project. On the one hand, the way in which visual sequences are represented in the analysis of open spaces is analyzed, transferring to the field of landscape the space-time approach that Giedion introduced for architecture in his influential book Space, Time and Architecture. On the other hand, representation systems to design landscape transformation processes are studied, from those associated with plant succession to those of a more structural nature, which transcend the scale of architectural design to be placed in the field of urban scale strategic plans.